Research Priorities in Traditional Persian Medicine - Morteza Mojahedi; Seyyed Ali Mozaffarpur; Mohammad Mahdi Isfahani; Mohsen Naseri; Mohammad Kamalinejad; Mahmoud Khodadoust; Mansoor Keshavarz; Gholamreza Amin; Ali Reza Abbassian; Abbas Najjari; Arman Zargaran; Majid Asghari; et al. (Journal of Research on History of Medicine, 2016)
Research is considered axis of each progressing and scientific development. Scattered studies without any logical plan won’t lead to the desired results. Research prioritization in Traditional Persian Medicine (TPM) is more necessary because of limited resources and manpower.This study was conducted in four phases with Delphi’s pattern of study. At the first stage, it was consulted from TIM departments at universities in Iran about research priorities. Conclusion of these priorities due to scoring to them was sent for 160 experts and assistants of traditional medicine, in two phases. For the last step, results of previous steps and conclusion of two phases of scoring were reviewed by the outstanding masters of TIM. The result was categorized, concluded and then presented in table form.81 topics were determined as research priorities after the conclusion of all comments. These topics are categorized in 4 areas. 3 topics in the area of “Hefz-al-Sehhah” (Maintaining the health), 12 subject in the area of “effective factors on sustainable development of Traditional Medicine”, 3 topics in “Basics of TIM “ and 65 subjects in the field of “diseases”.It is proposed that the arrangement of research priorities be considered in “Hefz-al-Sehhah”, “effective factors on sustainable development of Traditional Medicine”, “Basics of TIM” and “diseases” consequently. We recommend that research groups in the proposed areas to be formed, designing a research strategy for each area by sequential studies to achieve definite goals. It is suggested that research policy-making entities in the field of TIM and also related scientific associations, use these research priorities as the basis for moral and financial support.